2012
DOI: 10.1111/j.1469-7998.2012.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual quality and nuptial throat colour in male European green lizards

Abstract: Nuptial traits signalling individual quality are common in numerous animal taxa, and play a significant role in sexual selection. Detecting female mate choice based on visual cues is notoriously hard in lizards. Previously, we found that female European green lizards (Lacerta viridis) preferred to associate with males with high ultraviolet (UV) throat reflectance. Here, we investigated if different components of nuptial throat colour of male European green lizards were correlated to other fitness-related trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…Because chameleon display coloration and change has never been quantitatively analysed with respect to intraspecific variation in behaviour, we measured the amount and speed of colour change, as well as maximum display brightness ( previously suggested to be an informative component of squamate colour signals [16]). We measured colour changes as: (i) the perceptual distance travelled (sum of distances between colour measurements taken at different times) and (ii) rate of colour change ( perceptual distance/time), both measured using units of just noticeable differences, which capture perceivable changes in colour taking into account species-specific photoreceptor sensitivities [13,17] (see electronic supplementary material, S4).…”
Section: Methodsmentioning
confidence: 99%
“…Because chameleon display coloration and change has never been quantitatively analysed with respect to intraspecific variation in behaviour, we measured the amount and speed of colour change, as well as maximum display brightness ( previously suggested to be an informative component of squamate colour signals [16]). We measured colour changes as: (i) the perceptual distance travelled (sum of distances between colour measurements taken at different times) and (ii) rate of colour change ( perceptual distance/time), both measured using units of just noticeable differences, which capture perceivable changes in colour taking into account species-specific photoreceptor sensitivities [13,17] (see electronic supplementary material, S4).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, year‐specific environmental conditions may exert major influences on sexual signal expression (Saino et al ., ; Molnár, Bajer & Török, ; Scordato, Bontrager & Price, ) and there may be different year‐specific effects on different ornaments of the same species (Hegyi et al ., ). This may cause among‐year variation in the magnitude and pattern of integration among multiple ornamental traits.…”
Section: Introductionmentioning
confidence: 99%
“…Production and maintenance of structural colors have been shown to be energetically costly (Megía‐Palma, Martínez, & Merino, ; Prum, ), with both developmental stress and available nutrients influencing coloration in lizards (Olsson et al., ). Additionally, previous studies showed that nuptial throat coloration is condition dependent (Molnár et al., ) and affected by environmental factors (Bajer et al., ) in the study species. Previously, it was found that the development of the throat patch color right after the hibernation was affected by basking time and not by available energy (Bajer et al., ).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, structural coloration (blue and ultraviolet (UV)) is caused by light scattering and/or reflective microstructures in the dermal tissue (Olsson, Stuart‐Fox, & Ballen, ). Intense sexual coloration may increase predation risk (Pascual, Senar, & Domenech, ) and conspecific aggression (Kotiaho, ) and the production of both types of color signals can be energetically costly (Grether et al., ; Hurst, ) and condition dependent (Keyser & Hill, ; Molnár, Bajer, Török, & Herczeg, ). It has been demonstrated in a wide range of taxa that environmental constraints affecting survival and reproduction of animals can significantly influence expression and evolution of pigment based color signals (Blanco, Frias, Garrido‐Fernandez, & Hornero‐Mendez, ; Casagrande, Costantini, Tagliavini, & Dell'Omo, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation